Influence of Concomitant Extracranial Injury on Functional and Cognitive Recovery From Mild Versus Moderate to Severe Traumatic Brain Injury. Issue 6 (November 2020) - Carroll, Ellen L.; Manktelow, Anne E.; Outtrim, Joanne G.; Chatfield, Doris; Forsyth, Faye; Hutchinson, Peter J. A.; Tenovuo, Olli; Posti, Jussi P.; Wilson, Lindsay; Sahakian, Barbara J.; Menon, David K.; Newcombe, Virginia F. J.
Abstract : Objective: To determine the effect of extracranial injury (ECI) on 6-month outcome in patients with mild traumatic brain injury (TBI) versus moderate-to-severe TBI. Participants/Setting: Patients with TBI ( n = 135) or isolated orthopedic injury ( n = 25) admitted to a UK major trauma center and healthy volunteers ( n = 99). Design: Case-control observational study. Main Measures: Primary outcomes: ( a ) Glasgow Outcome Scale Extended (GOSE), ( b ) depression, ( c ) quality of life (QOL), and ( d ) cognitive impairment including verbal fluency, episodic memory, short-term recognition memory, working memory, sustained attention, and attentional flexibility. Results: Outcome was influenced by both TBI severity and concomitant ECI. The influence of ECI was restricted to mild TBI; GOSE, QOL, and depression outcomes were significantly poorer following moderate-to-severe TBI than after isolated mild TBI (but not relative to mild TBI plus ECI). Cognitive impairment was driven solely by TBI severity. General health, bodily pain, semantic verbal fluency, spatial recognition memory, working memory span, and attentional flexibility were unaffected by TBI severity and additional ECI. Conclusion: The presence of concomitant ECI ought to be considered alongside brain injury severity when characterizing the functional and neurocognitive effects of TBI, with each presenting challenges to recovery. Abstract : Supplemental Digital Content is Available in the Text.